KIDNEY STONES: ETIOLOGY, PATHOGENESIS, AND TREATMENT METHODS (International journal of medical sciences, 2026)
Kidney stones (urolithiasis) are one of the most common diseases of the urinary system and develop under the influence of metabolic, infectious, and environmental factors. The disease may present with pain syndrome, urinary dysfunction, and various complications. This article analyzes the mechanisms of kidney stone formation, risk factors, clinical manifestations, and modern diagnostic and treatment methods.